Revegetation has increased ecosystem water-use efficiency during 2000–2014 in the Chinese Loess Plateau: Evidence from satellite data. (July 2019) - Zheng, Han; Lin, Henry; Zhou, Weijian; Bao, Han; Zhu, Xianjin; Jin, Zhao; Song, Yi; Wang, Yunqiang; Liu, Wenzhao; Tang, Yakun
Highlights: Indicator of water-use efficiency (WUE) in the Chinese Loess Plateau (CLP) is investigated. Annual WUE and autumn WUE significantly increased in the CLP during 2000–2014. The less humid areas in the CLP generally have lower annual WUE values but higher values over active growing season. Vegetation coverage change was the primary cause driving temporal variations in annual WUE in the CLP. Abstract: Vegetation coverage has been effectively increased across the Chinese Loess Plateau (CLP) mainly because of the implementation of large-scale revegetation programs. Understanding the entire CLP's ecosystem carbon-water relationship and its response to the vegetation coverage increase and climate change is essential for the water resources management in this semi-humid to arid region. Water-use efficiency (WUE), defined as the ratio of gross primary productivity (GPP) over evapotranspiration (ET), is an important indicator linking carbon and water cycles at the ecosystem scale. In this study, the spatial and temporal variations in the ecosystem WUE were analyzed to investigate the responses of WUE variation to regional climate and vegetation coverage changes in the CLP using MODerate Resolution Imaging Spectroradiometer (MODIS) datasets of GPP and ET from 2000 to 2014. Results indicate that the spatial pattern of annual WUE was different from that of WUE over active growing season (AGS), generally with higher annual WUE but lower AGS-WUE for the semi-humid southeastern CLP areas. Significant increases were observed in annual and autumn WUE during the study period at both the per-pixel and spatial-average levels, while AGS-WUE, spring WUE, and summer WUE remained quite stable. Correlations between WUE trends and interannual variability of vegetation coverage (expressed as Normalized Difference Vegetation Index or NDVI), precipitation ( P ), and air temperature ( T a ) showed that WUE trends were positively correlated with NDVI variation due to faster increases in GPP as compared to ET caused by enhanced NDVI. Precipitation variation was generally negatively correlated to WUE variation by contributing to faster increases in ET than GPP especially at different seasons. The positive correlations between interannual variability of WUE and T a were subject to negative feedbacks between ET and T a . Similar results were also found using net primary productivity (NPP) to calculate ecosystem annual WUE (i.e., NPP/ET). Our findings suggest that revegetation-induced vegetation coverage change rather than P and T a changes is the primary cause for the increasing ecosystem annual WUE in the CLP. This study contributes to our enhanced understanding of the coupled carbon-water dynamics over regional terrestrial ecosystem under climate and vegetation coverage changes.